Implementasi Nilai-Nilai Pancasila Pada Sila Ke 5 Oleh Pegawai Di Kantor Urusan Agama Medan Johor - Muhammad Zuhri, Muftia Jannah, Arif Prabowo, Elma Sari Pane, Khairani (LPPPI Publishing, 2022)
Pancasila, which is the basis of the Republic of Indonesia, certainly has values ??that uphold the spirit of the state and also a sense of love for the Indonesian state. Looking at the five precepts of Pancasila, there is one principle that really upholds the value of diversity and togetherness, namely the fifth principle which reads